Laparoscopic Proximally Extended Colorectal Resection With Two-Stage Turnbull-Cutait Pull-Through Coloanal Anastomosis for Late Complications of Chronic Radiation Proctopathy - He, Yanjiong; Zhou, Zuolin; Huang, Xiaoyan; Guan, Qi; Qin, Qiyuan; Zhu, Miaomiao; Wang, Huaiming; Zhong, Qinghua; Chen, Daici; Wang, Hui; Fang, Lekun; Ma, Tenghui (Frontiers in Surgery, 2022)
Background: Chronic radiation proctopathy (CRP) is a common complication after radiation therapy for pelvic malignancies. Compared with diversion surgery, resection surgery removes the damaged tissue completely to avoid the risks of recurrence and improve patients’ outcome. Hence, resection surgery could be an optimal surgical approach when CRP is complicated by late complications. This study aimed to describe a modified surgical procedure of resection surgery and report its preliminary efficacy and safety in treating CRP patients with late complications. Methods: We retrospectivly reviewed the patients who were diagnosed with CRP with late complications and underwent the modified surgical procedure of laparoscopic proximally extended colorectal resection with two-Stage turnbull-cutait pull-through coloanal anastomosis (PE-Bacon) between November 2019 and October 2020 in the Sixth Affiliated Hospital of Sun Yat-sen University. Results: A total of 15 patients were performed the modified laparoscopic procedure of PE-Bacon, of which 1 patient underwent conversion from laparoscopic to open operation for intraoperative massive hemorrhage. Overall, the major (Clavien-Dindo Ⅲ-Ⅴ) postoperative complications occurred in 1 patient, anastomotic leakage was observed in 2 (13.3%) patients and anastomotic stricture was observed in 4 (26.7%) patients. No patient had to be reoperated and died. Up to now, at the average follow-up of (524.40±108.39) days, the preoperative symptoms of 93.3% (14/15) patients were relieved, with 9 patients achieved complete remission, 5 patients only suffered minor symptoms. 1 patient was still suffered vesicovaginal fistula as pre-operation because of the progression of radiation uropathy. Colostomy reversal has been performed on 8 (53.3%) patients at average postoperative 299.5±92.68 days, among whom only 2 patients suffered from major Low Anterior Resection Syndrome (LARS) until now. Conclusions: Laparoscopic PE-bacon surgery is a safe and feasible surgical procedure for late complications of chronic radiation proctopathy with low morbidity and high symptom remission rate.